"When the Last Shriek Has Died Away": On Orson Welles's Doctor Faustus and the Memory of Popular Theatre. Issue 3 (September 2022) - Vatain-Corfdir, Julie
Abstract : In 1927, Orson Welles directed Marlowe's Doctor Faustus for the Federal Theatre Project, in an original interpretation of Hallie Flanagan's dream of a "people's theatre." While the available archives allow for an examination of Welles's experiment in popular classicism and invite comparisons with the work of French theatre-makers, they also call for an awareness of the part played by our imagination in such retrospective research.